2016
DOI: 10.1002/adma.201601505
|View full text |Cite
|
Sign up to set email alerts
|

Efficient All‐Vacuum Deposited Perovskite Solar Cells by Controlling Reagent Partial Pressure in High Vacuum

Abstract: All-vacuum-deposited perovskite solar cells produced by controlling reagent partial pressure in high vacuum with newly developed multi-layer electron and hole transporting structures show outstanding power conversion efficiency of 17.6% and smooth, pinhole-free, micrometer-sized perovskite crystal grains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 25 publications
2
120
1
Order By: Relevance
“…[35] We believe VASP methods hall be able to fabricate mixed cation and multiple halide materials with high quality.I no ur future works, we will try to fabricatem ix-cation and pseudohalide-based perovskite by our LP-VASP. After few years research, the mixcation and halide-based perovskite structure can make great perovskite crystal, which is not yet totally explored by the VASP method.…”
Section: Resultsmentioning
confidence: 99%
“…[35] We believe VASP methods hall be able to fabricate mixed cation and multiple halide materials with high quality.I no ur future works, we will try to fabricatem ix-cation and pseudohalide-based perovskite by our LP-VASP. After few years research, the mixcation and halide-based perovskite structure can make great perovskite crystal, which is not yet totally explored by the VASP method.…”
Section: Resultsmentioning
confidence: 99%
“…82,84 In general, perovskite vacuum deposition is divided in two different methods: (1) The inorganic layer (PbX 2 , X = I, Br, Cl) is coated by a solvent engineering technique and the organic component (e.g., MAI or FAI) is evaporated 14,52,83 and (2) both organic and inorganic components are evaporated. 37,82 Hsiao et al, 37 reported a full vacuum deposited solar cell with PCEs of 15%-17% (0.1 cm 2 ). The authors determined that device performance depends significantly on the organic halide partial pressure.…”
Section: Ink-jet Printing Vacuum/vapor Deposition and Other Large Armentioning
confidence: 99%
“…Several studies in the literature show how methylammonium iodide vapour as a second step over PbI 2 films can create a smooth perovskite layer as an alternative to dip-coating. 12,14,37 An alternative option as a second step consists in spray coating the methylammonium iodide solution over the lead iodide layer 38,39 (see Figure 3(c)). 40 A comparison between perovskite layers obtained by dip-coating and spray coating of the methylammonium solution revealed a better morphology for the spray coated sample (Figures 3(d) and 3(e)) 40 and PCEs of up to 14.3% achieved.…”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Hsiao et al reported HOIP solar cells of 17.6% with photovoltaic parameters of 1.06 V, 22.7 mA/cm 2 , and fill factor of 0.73, which currently is the best record efficiency for vapor-based techniques. 30 By manipulating the partial pressure of organic halide vapor during the sequential evaporation process, it was found that the metal halide film can fully convert into perovskite only at a pressure range 10 −3 -10 −4 Torr in 2 h. Perovskite films with smooth surface and crystallite size of micrometer were obtained under vapor pressure of 10 −4 Torr. At low pressure of 10 −5 Torr, the transformation of metal halide into perovskite is incomplete.…”
mentioning
confidence: 99%